Arterial Puncture Using Insulin Needle Is Less Painful Than With Standard Needle: A Randomized Crossover Study. (2nd March 2015) - Ibrahim, Irwani; Yau, Ying Wei; Ong, Lizhen; Chan, Yiong Huak; Kuan, Win Sen; Hiestand, Brian
Abstract Objectives Arterial punctures are important procedures performed by emergency physicians in the assessment of ill patients. However, arterial punctures are painful and can create anxiety and needle phobia in patients. The pain score of radial arterial punctures were compared between the insulin needle and the standard 23‐gauge hypodermic needle. Methods In a randomized controlled crossover design, healthy volunteers were recruited to undergo bilateral radial arterial punctures. They were assigned to receive either the insulin or the standard needle as the first puncture, using blocked randomization. The primary outcome was the pain score measured on a 100‐mm visual analogue scale (VAS) for pain, and secondary outcomes were rate of hemolysis, mean potassium values, and procedural complications immediately and 24 hours postprocedure. Results Fifty healthy volunteers were included in the study. The mean (±standard deviation) VAS score in punctures with the insulin needle was lower than the standard needle (23 ± 22 mm vs. 39 ± 24 mm; mean difference = –15 mm; 95% confidence interval = –22 mm to –7 mm; p < 0.001). The rates of hemolysis and mean potassium value were greater in samples obtained using the insulin needle compared to the standard needle (31.3% vs. 11.6%, p = 0.035; and 4.6 ±0.7 mmol/L vs. 4.2 ±0.5 mmol/L, p = 0.002). Procedural complications were lower in punctures with the insulin needle both immediately postprocedure (0% vs. 24%; p < 0.001) and at 24 hours postprocedure (5.4% vs. 34.2%; p = 0.007). Conclusions Arterial punctures using insulin needles cause less pain and fewer procedural complications compared to standard needles. However, due to the higher rate of hemolysis, its use should be limited to conditions that do not require a concurrent potassium value in the same blood sample.